BALANCE OF CONSUMPTION WITH ALMS IN ISLAMIC ECONOMIC LAW ETHICS - Doli Witro; Syahrul Anwar (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2021)
In Islam, consumption is interpreted as fulfilling spiritual and physical needs that aim to maximize the function of humanity as a servant of Allah s.w.t. in obtaining happiness and prosperity in this world and the hereafter (falah). Islam also advocates the distribution of prosperity and economic opinion in society. One of the Islamic solutions to distribute economic prosperity and people’s income is alms. This paper discusses the balance between consumption and alms in the view of sharia economic law ethics. This article aims to determine the balance between consumption and alms in the ethics of sharia economic law. This article is qualitative research with library research. The data in this study were obtained from library materials such as books, journals, etc. The data writing technique used is a data analysis technique known by Miles et al., namely data condensation, data presentation, and drawing conclusions. The results of the study show that in creating a balance between alms and consumption in the ethics of sharia economic law, humans must be able to distinguish between needs and desires, humans must also prioritize self, family, and social benefits, humans are prohibited from justifying what is stipulated as haram and forbidding anything lawful.